Shifting gears versus sudden stops: qualitative study of consultations about driving in patients with cognitive impairment - Colin Bradley; Carol Sinnott; Tony Foley; Linda Horgan; Kathleen McLoughlin; Cormac Sheehan (BMJ Open)
Objective General practitioners (GPs) report finding consultations on fitness to drive (FtD) in people with cognitive impairment difficult and potentially damaging to the physician–patient relationship. We aimed to explore GP and patient experiences to understand how the negative impacts associated with FtD consultations may be mitigated.Methods Individual qualitative interviews were conducted with GPs (n=12) and patients/carers (n=6) in Ireland. We recruited a maximum variation sample of GPs using criteria of length of time qualified, practice location and practice size. Patients with cognitive impairment were recruited via driving assessment services and participating general practices. Interviews were audio-recorded, transcribed and analysed thematically by the multidisciplinary research team using an approach informed by the framework method.Results The issue of FtD arose in consultations in two ways: introduced by GPs to proactively prepare patients for future driving cessation or by patients who urgently needed a medical report for an expiring driving license. The former strategy, implementable by GPs who had strong relational continuity with their patients, helped prevent crisis consultations from arising. The latter scenario became acrimonious if cognition had not been openly discussed with patients previously and was now potentially impacting on their right to drive. Patients called for greater clarity and empathy for the threat of driving cessation from their GPs.Conclusion GPs used their longitudinal relationship with cognitively impaired patients to reduce the potential for conflict in consultations on FtD. These efforts could be augmented by explicit discussion of cognitive impairment at an earlier stage for all affected patients. Patients would benefit from greater input into planning driving cessation and acknowledgement from their GPs of the impact this may have on their quality of life.